sealer
sealer 1 n He took the TERRA NOVA in preference to the DISCOVERY. In 1914 Bowring Brothers bought her from the Admiralty, and ever since then she has been a Newfoundland sealer. PRINTED ITEM DNE-cit [-]Newfoundland[-] Used I Used I 1 Not used siler,soiler,swiler,swoiler,LANDSMAN. Source not listed but stamped.